THE INFLUENCE OF PRODUCT QUALITY TOWARD PURCHASE DECISION BASED ON CONSUMER PERCEPTION - Indah Bayunitri, Bunga (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to examine the product quality for purchasing decisions based on consumer perceptions. This research uses quantitative research methods with the object being taken from the consumer of Kopi Toko Djawa. The sampling technique used in this research is a random sample technique. Based on results, product quality has an influence on purchasing decisions based on consumer perception of 85.5%. This shows that the better the quality of the product, the better the purchasing decision.